Stress Profile in a Two-Dimensional Silo: Effects Induced by Friction Mobilization - Melo-Hurtado, F; Vivanco-Avaria, F (American Physical Society, 2016)
The effects of friction mobilization on the stress profile within a two-dimensional silo are investigated via simulations of discrete elements. Friction mobilization is driven by cyclic vertical displacement of the sidewalls. Two regimes have been observed for small filling height, with stress profiles identified as saturated (Janssen s profile) and exponentially growing. The transition between these regimes is denoted by an almost linear stress profile, similar to that of a hydrostatic system, with a significantly greater characteristic height compared to the height of the column of grains. For tall columns, the process of friction inversion is more complex. A partial inversion of friction mobilization is observed when the motion is reversed from upward to downward, which results in two coexisting zones of opposite mobilization. These zones are separated by a wide compaction front with a gradual upward progression sustained by the displacement of the walls. Conversely, if the motion is reversed, the two opposing friction mobilization zones retract, the transition zone becomes smooth, and the system rapidly transforms from two coexisting mobilization states to a Janssen-like regime. In both regimes, the general characteristics from the resulting stress profiles are depicted by generalizing Janssen s equation to include partial mobilization through the varying effective friction coefficient along the silo walls. © 2016 American Physical Society.